Crack initiation mechanisms during very high cycle fatigue of Ni-based single crystal superalloys at high temperature. (15th April 2020) - Cervellon, A.; Hémery, S.; Kürnsteiner, P.; Gault, B.; Kontis, P.; Cormier, J.
Abstract: Crack initiation mechanisms in the very high cycle fatigue (VHCF) regime of nickel-based single-crystal (SX) superalloys have been investigated at high temperature (1000 °C) and under fully reversed conditions ( R = −1). For all Ni-based SX alloys tested, a discernible area called rough zone has been identified around the crack initiation site on the fracture surface and is for the first time described. By means of electron microscopy and atom probe analyses, localized and severe plastic activity occurring in the rough zone is evidenced. The high dislocation density provided by the slip bands induces single-phase recrystallized grains and phases precipitation (intermetallics or carbides) via the redistribution of interacting solutes in the rough zone. A crack initiation mechanism based on these observations and on the stress intensity parameter determined around the rough zone – which has been demonstrated to be a constant threshold dependent on the material – is finally proposed. Graphical abstract: Image, graphical abstract